Genetic Parameters for First Lactation and Lifetime Traits of Nili-Ravi Buffaloes - Tamboli, Pooja; Bharadwaj, Anurag; Chaurasiya, Amit; Bangar, Yogesh Chandrakant; Jerome, Andonissamy (Frontiers in Veterinary Science, 2021)
The data on first lactation and lifetime performance records of 501 Nili-Ravi, were collected for a period from 1983 to 2017 (35 year) maintained at ICAR-Central Institute for Research on Buffaloes, Sub-Campus, Nabha, Punjab. The data were analysed to calculate heritability, genetic and phenotypic correlation for first lactation traits viz., Age at First Calving (AFC), First Lactation Total Milk Yield (FLTMY), First Lactation Standard (305 days or less) Milk Yield (FLSMY), First Peak Milk Yield (FPY), First Lactation Length (FLL), First Dry Period (FDP), First Service Period (FSP) and First Calving Interval (FCI), Herd Life (HL), Productive Life (PL), Productive Days (PD), Unproductive Days (UD), Breeding Efficiency (BE), Total Lifetime Milk Yield (Total LTMY), Standard Lifetime Milk Yield (Standard LTMY), Milk Yield Per Day of Productive Life (MY/PL), Milk Yield Per Day of Productive Days (MY/PD), Milk Yield Per Day of Herd Life (MY/HL). For estimation of variance component and heritability separately for each trait, the uni-trait animal model was equipped, whereas to estimate genetic and phenotypic correlations between traits, bi-trait animal models were fitted. The estimates of heritability for production and reproduction traits of Nili-Ravi were medium i.e. 0.365±0.087, 0.353±0.071, 0.318±0.082,0.354±0.076 and 0.362±0.086 for FLSMY, FDP, FSP, FCI and AFC, respectively. The estimates of heritability were low i.e.0.062±0.088, 0.123±0.090, 0.158±0.090, 0.155±0.091 and 0.129±0.091 for HL, PL, PD, Total LTMY and Standard LTMY and high i.e.0.669±0.096 for BE. Genetic correlation for FLTMY was high with FLL (0.710±0.103) and genetic correlation of FLTMY was high and positive with HL, Total LTMY, MY/PL, MY/PD while low and positive with PL. Genetic correlation of AFC was low and negative with PL, PD, UD, BE, Total LTMY, Standard LTMY, MY/PL and MY/PD and negative with MY/HL. Significant positive phenotypic association of FPY was seen with FLTMY, FLSMY, FLL, AFC, HL, Total LTMY and Standard LTMY. Higher heritability of first lactation traits specially FPY suggest sufficient additive genetic variability which can be exploited under selection and breeding policy in order to improve overall performance of Nili-Ravi buffaloes.